Relationship of Managerial Creativity and Organizational Effectiveness With Population Characterization: Exploring the Link between Managerial Creativity and Organizational Effectiveness in a Dynamic Population (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Organizational Effectiveness is one of the most complexand least tackled in the study of social organizations. In simple terms,organizational effectiveness is an organization’s ability to maximize resultsin the competitive external environment. The concept of organizationaleffectiveness is an important innovation in business management. Initially,organizational effectiveness focused on how well an organization compete, howquickly they bring products to the market, their status in the community, theirattractiveness to potential market and their profitability. In other words,organizational effectiveness considers how well an organization performsbusiness. Instead of defining corporate success by a few short-term measures,such as sales or profit, it fostered a holistic long-term perspective. Thisexpanded perspective that resulted from a focus on the overall effectiveness ofan organization has become central to corporate survival and success in today’seconomy. The focus on people, their performance, innovation and creativity isthe professional concern of organizational effectiveness. The current researchattempts to define a broad perspective on organizational effectiveness and itsrelation to managerial creativity.